Peningkatan Pengetahuan Ibu Nifas Tentang Personal Hygiene - Mafudiah, Lalita; Vistra Veftisia (Universitas Ngudi Waluyo, 2024)
The puerperium period begins 2 hours after the birth of the placenta until 6 weeks (42 days) after that. puerperium is from the word puer which means baby and Parous means to give birth. So, puerpurium means the period after giving birth to the baby, which is the period of recovery, starting from the time the delivery is completed until the uterine apparatus returns like pre- pregnancy(Handayani, Rini & Mulyati, Sri, 2117). One of the needs during the postpartum period is to maintain personal hygiene. Personal hygiene is an activity to meet daily needs, which can be known as daily life activities. This activity is learned over time and becomes a lifelong habit. Personal hygiene activities involve not only what to do (personal hygiene of bathing, dressing, toilet and eating) but also how much, when, where, with whom and how(Wati, 2023). From the results of the study in East Jomin Village, there are 10 postpartum mothers, of which 5 of the postpartum mothers do not do Personal Hygiene due to the lack of knowledge of mothers about Personal Hygiene. Based on the problems that arise, community service activities are needed to overcome this. The activity began with a pre-test related to Personal Hygiene during the postpartum period, then the delivery of material counseling method with a total of 10 postpartum mothers. The next activity is evaluation with Post-Test. From these activities, there was an increase in the knowledge of postpartum mothers after being given counseling on Personal Hygiene. Abstrak Masa nifas (puerperium) adalah dimulai sejak 2 jam setelah lahirnya Plasenta sampai dengan 6 minggu (42 hari) setelah itu. puerperium yaitu dari kata puer yang artinya bayi dan Parous artinya melahirkan. Jadi, puerpurium berarti masa setelah melahirkan bayi yaitu masa pulih kembali, mulai dari persalinan selesai sampai alat alat kandungan kembali seperti pra hamil (Handayani, Rini & Mulyati, Sri, 2117). Salah satu kebutuhan pada masa nifas yaitu menjaga kebersiahan diri (Personal Hygiene). Personal hygiene merupakan aktivitas untuk memenuhi kebutuhan sehari-hari, yang bisa dikenal dengan aktivitas kehidupan sehari-hari. Aktivitas ini dipelajari dari waktu ke waktu dan menjadi kebiasaan seumur hidup. Kegiatan personal.